BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2002)
Dynamics of Plant diseses by S. Nagarajan andÂ K. Muralidharan (1995). Allied Publishers Ltd.Â New Delhi. pp. 218. Rs. 4501-ISBN81-7023-4379. Bemisia tabaci (Genuadius) : Crop Pest andÂ Principal Wllitefly Vector of Plant VirusesÂ (1995), Basu, A.N., Oxford & IBH Publishing Co.Â Pvt. Ltd., New Delhi, V + 183 pp, 25.0 cm x 16.5Â cm. Its. 550/-, ISBN 81-204-0984-1. Agricultural and Forest Pests and their ManagementÂ (1995), By Prem Chand, Oxford & IBHÂ Publishing Co. Pvt. Ltd. 66 Janpath, New Delhi,Â 24cm x 15.5 em XVI + 374 Rs. 64/-, ISBN 81-204-0945-0. Â